2014
DOI: 10.1038/hortres.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses of creeping bentgrass (Agrostis stolonifera) to elevated carbon dioxide concentrations

Abstract: The atmospheric carbon dioxide level has increased and is predicted to continue increasing, which may affect various aspects of plant growth. The objective of this study was to investigate the effects of doubling the carbon dioxide level on the growth and physiological activities of a widely utilized cool-season turfgrass species, creeping bentgrass (Agrostis stolonifera L. ‘Penncross’). ‘Penncross’ plants were established in fritted clay medium and maintained under well-irrigated and well-fertilized condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
(4 reference statements)
3
30
0
Order By: Relevance
“…But when the plants were exposed on increased atmospheric CO 2 the final plant biomass, above ground biomass and below ground biomass was significantly increased in tree species (Madhu & Hatfield 2013). Similarly, the shoot biomass was approximately 35% greater for creeping bentgrass plants grown under elevated CO 2 compared to plants maintained under ambient CO 2 , while the root biomass increased by 37% due to elevated CO 2 (Burgess & Huang 2014). Wang et al (2015) studied the responses of rice production under elevated CO 2 , there was significant stimulation in above ground biomass 28 per cent and below ground biomass of rice was 42 per cent increases.…”
Section: Results and Discussion A) Response Of Azadirachta Indica Tomentioning
confidence: 90%
“…But when the plants were exposed on increased atmospheric CO 2 the final plant biomass, above ground biomass and below ground biomass was significantly increased in tree species (Madhu & Hatfield 2013). Similarly, the shoot biomass was approximately 35% greater for creeping bentgrass plants grown under elevated CO 2 compared to plants maintained under ambient CO 2 , while the root biomass increased by 37% due to elevated CO 2 (Burgess & Huang 2014). Wang et al (2015) studied the responses of rice production under elevated CO 2 , there was significant stimulation in above ground biomass 28 per cent and below ground biomass of rice was 42 per cent increases.…”
Section: Results and Discussion A) Response Of Azadirachta Indica Tomentioning
confidence: 90%
“…Plants respond positively to increases in atmospheric CO 2 with increased growth and improved water use efficiency . Creeping bentgrass response to increased CO 2 (400 vs. 800 μmol mol -1 ) exhibited a faster growth rate of lateral stems and increased shoot and root dry weights with reduced specific leaf area (Burgess and Huang, 2014). Net photosynthetic rates increased, along with reduced stomatal conductance and transpiration rate which improved water use efficiency with a greater effect in C 3 compared to C 4 species.…”
Section: Carbon Dioxide Impactsmentioning
confidence: 84%
“…Substantial increases in leaf photosynthetic rates were reported in perennial ryegrass, tall fescue, and Kentucky bluegrass (Rogers et al., ; Song et al., ; Yu, Chen, Xu, & Huang, ) when CO 2 concentrations were doubled (800 ppm). Burgess and Huang (,b) also noted significant increases in net photosynthetic rates of creeping bentgrass. These were attributed to either the higher availability of CO 2 or the improved activation state of Rubisco.…”
Section: Effects Of Elevated Co2 On Cool‐season Grass Physiologymentioning
confidence: 90%
“…Fu and Dernoeden () found no significant effect of mild water stress on whole‐plant respiration rates of tall fescue plants. However, in a later study, Burgess and Huang (,b) reported that metabolites, involved in the tricarboxylic acid cycle of dark respiration, were downregulated in roots of drought‐stressed creeping bentgrass plants, indicating a decrease in root dark respiration rates under limited water supply conditions.…”
Section: Effects Of Drought Stress On Cool‐season Grass Physiologymentioning
confidence: 96%
See 1 more Smart Citation